Multi-Agent Systems: A Tool in Spatial Planning. An Example of Micro-Simulation Use in Retail Development. - Leeuwen, Eveline S. van; Hagens, Janneke E.; Nijkamp, Peter (TH Zürich, NSL, 2007)
Die Autoren diskutieren die Möglichkeiten Agenten-basierter Modelle in den Planungswissenschaften. Der Artikel enthält sowohl einen allgemein gehaltenen Überblick, der als Einführung dienen kann und soll, als auch die Beschreibung eines Modells, das die Auswirkungen eines neuen großen Einkaufszentrums untersucht. Veränderte Verkehrsströme sind hier die Auswirkungen von verändertem Verhalten (z.B. Wahl eines anderen Einkaufsorts und/oder Wahl einer anderen Einkaufszeit), und diese Verhaltensänderungen können direkt im Modell abgebildet werden, weil die Menschen im Modell als individuelle Einheiten enthalten sind. difu

In planning research and practice, many different tools are used to understand spatial situations. As Multi-Agent Systems (MAS) are models that can include communicative qualities along with more analytical qualities, we argue that it can be a useful tool in spatial planning. Therefore, the aim of the paper is to show the possibilities of multi-agent systems (MAS) in spatial analysis and decision-making processes in the field of spatial planning. We illustrate its potential by discussing a basic example of spatial retail developments at a local scale in the Netherlands. The conclusion is that MAS, in fact, can include relevant analytical qualities that are missing in other instruments. Particularly, the power of showing spatial dynamics and relations, and as such providing "relatively reliable" information about complex (future) spatial developments, can be seen as an analytical and communicative quality, which can be very useful in spatial planning. difu
Keywords: Raumplanung; Verkehrsplanung; Planung; Planungsinstrument; Einkaufszentrum; Simulation; Verhalten; Fallstudie; Planungswissenschaft; Modellsimulation; Mikrosimulation; Verkehrsstrom; Einkaufsverkehr